Nutrition literacy is associated with general obesity, abdominal obesity, and body fat percentage obesity - Cui, Yan; Qi, Qi; Sun, Yuhui; Liu, Rumeng; Yin, Wending; Liu, Huaqing (Frontiers in Nutrition, 2025)
BackgroundObesity is associated with unhealthy eating behavior among adults. Nutrition literacy (NL) is an important determinant of eating behavior. This study investigated the association of NL with general obesity, abdominal obesity, and body fat percentage (BFP) obesity among adults.MethodsThis study was a cross-sectional survey on the Nutrition Literacy and Obesity, conducted in Bengbu City, China (May to July 2023). The Short-Form Nutrition Literacy scale was used to evaluate the NL of adults. General obesity was defined as a body mass index of ≥28 kg/m2. Abdominal obesity was defined as a waist circumference of ≥90 cm in men and ≥85 cm in women. BFP obesity was defined as a BFP of ≥30% in men and ≥42% in women. Binary logistic regression analysis was performed to identify the correlations of NL with general obesity, abdominal obesity, and BFP obesity in adults. Subgroup analyses and interaction tests were also performed.ResultsParticipants with a high level of NL had low odds of general obesity (odds ratio [OR]: 0.66; 95% confidence interval [CI]: 0.43–0.99), abdominal obesity (OR: 0.63; 95% CI: 0.46–0.87), and BFP obesity (OR: 0.55; 95% CI: 0.35–0.87). In subgroup analyses and interaction tests, age significantly influenced the negative correlations of NL with abdominal obesity and BFP obesity (p for interaction <0.05), but not general obesity (p for interaction >0.05). Moreover, sex and smoking status significantly influenced the negative correlations of NL with general obesity and abdominal obesity (p for interaction <0.05), but not BFP obesity (p for interaction >0.05), and drinking status significantly influenced the negative correlations of NL with abdominal obesity (p for interaction <0.05), but not general obesity and BFP obesity (p for interaction >0.05). However, marital status did not significantly influence the correlation of NL with obesity (p for interaction >0.05).ConclusionOur findings highlight that adults with high levels of NL have low odds of general obesity, abdominal obesity, and BFP obesity. Age, sex, smoking status, and drinking status influence the correlation between NL and obesity. The results indicate the importance of NL in the prevention and management of obesity in adults. To effectively address the challenges of adult obesity management, public health practitioners should tailor nutrition education and skill training programs to specific demographic profiles.